COMMUNICATION TECHNOLOGIES AND MORAL QUANDARIES: A CHRISTIAN ETHICAL REFLECTION - Aina, Raymond Olusesan (Asian Horizons, 2016)
Technology, including digital information and communication technologies (DICT), is not morally neutral. It is built on a rejection of God and divine providence. Hence, it has no regard for theistic perspective; neither does it consider the bigger picture that classical philosophy and religion consider. Yet, DICT has demonstrated the potential to be a powerful driver of revolution and social change. Besides, the virtual reality created by DICT has somewhat helped to cushion the negative effects of loneliness and emotional instability caused by necessary physical separation. Nonetheless, the human community cannot be blind to DICT’s moral quandaries. How is DICT changing the understanding of common traditional notions like ‘selfhood’, ‘community’, ‘friends’, ‘truth’, and ‘fidelity’? Do we use these technologies to celebrate the height of human nobility, or we use them to descend into the abyss of immorality? At what point can we say ‘enough!’? Can we say ‘enough!’ again, or we are condemned to the technological imperative? These questions inspire this article’s reflection, from a Christian theological ethics perspective.